2009
DOI: 10.1042/bst0371050
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of lipid droplets in regulating longevity

Abstract: Growing evidence supports the view that LDs (lipid droplets) are dynamic organelles that can serve both as an intracellular signalling compartment and as an organizing platform orchestrating many vital processes in eukaryotic cells. It has become clear that the LDs-confined deposition and lipolytic degradation of neutral lipids define longevity in multicellular eukaryotic organisms and yeast. We summarize the evidence in support of the essential role that LDs play in longevity regulation and propose several mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 48 publications
1
82
0
Order By: Relevance
“…These cellular processes include the following: (1) glycogen degradation; (2) the glycolytic pathway; (3) the pentose phosphate pathway; (4) pyruvate conversion to acetyl-CoA; (5) the maintenance of redox balance between NAD and NADH with the help of carnitine and glycerol-3-phosphate shuttles; (6) ROS detoxification; (7) stress response; (8) glutathione synthesis; (9) gluconeogenesis; (10) ethanol formation; (11) the synthesis and hydrolytic degradation of triacylglycerols (TAG) and ergosteryl esters (EE), the 2 major neutral lipids; (12) the synthesis of various amino acids; (13) nucleotide synthesis; (14) the assembly of the 40S and 60S ribosomal subunits from numerous protein components whose levels were altered by LCA; and (15) proteasomal and vacuolar protein degradation. 4,5,39,41,38,71,72 We then subjected cellular proteins whose levels were changed in yeast grown in a medium supplemented with LCA to bioinformatic analysis with the help of the SPELL online search engine, 51 as described above for mitochondrial proteins. Just as our bioinformatic analysis of mitochondrial proteins revealed (see above), we found that each of the cellular proteins whose level was altered in yeast cultured with LCA belongs to the following 2 multi-clustered regulons: (1) the PMD regulon, which consisted of the rho 0 (Rtg2p governed) cluster, S1 cluster, general TCA cycle dysfunction cluster, kgd1D, kgd2D or lpd1D cluster, yme1Dmdl1D Figure 2.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
“…These cellular processes include the following: (1) glycogen degradation; (2) the glycolytic pathway; (3) the pentose phosphate pathway; (4) pyruvate conversion to acetyl-CoA; (5) the maintenance of redox balance between NAD and NADH with the help of carnitine and glycerol-3-phosphate shuttles; (6) ROS detoxification; (7) stress response; (8) glutathione synthesis; (9) gluconeogenesis; (10) ethanol formation; (11) the synthesis and hydrolytic degradation of triacylglycerols (TAG) and ergosteryl esters (EE), the 2 major neutral lipids; (12) the synthesis of various amino acids; (13) nucleotide synthesis; (14) the assembly of the 40S and 60S ribosomal subunits from numerous protein components whose levels were altered by LCA; and (15) proteasomal and vacuolar protein degradation. 4,5,39,41,38,71,72 We then subjected cellular proteins whose levels were changed in yeast grown in a medium supplemented with LCA to bioinformatic analysis with the help of the SPELL online search engine, 51 as described above for mitochondrial proteins. Just as our bioinformatic analysis of mitochondrial proteins revealed (see above), we found that each of the cellular proteins whose level was altered in yeast cultured with LCA belongs to the following 2 multi-clustered regulons: (1) the PMD regulon, which consisted of the rho 0 (Rtg2p governed) cluster, S1 cluster, general TCA cycle dysfunction cluster, kgd1D, kgd2D or lpd1D cluster, yme1Dmdl1D Figure 2.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
“…IT IS INCREASINGLY CLEAR THAT LIPID DROPLETS (LD) are dynamic organelles with regulatory roles in many cellular processes besides lipid metabolism, including cell signaling, immune function, membrane trafficking, and regulation of longevity (42,70). Whereas the mechanism of these processes is only partially understood, much less is known about how the structure of the LD phospholipid monolayer may affect LD protein targeting and function.…”
mentioning
confidence: 99%
“…Taken together, results indicate that perilipin and associated lipolytic enzymes target areas in the phospholipid monolayer that are highly organized and rigid, similar in structure to localized areas of the PM where cholesterol and fatty acid uptake and efflux occur. lipolysis; caveolae; caveolin; concanavalin-A; adipose differentiationrelated protein IT IS INCREASINGLY CLEAR THAT LIPID DROPLETS (LD) are dynamic organelles with regulatory roles in many cellular processes besides lipid metabolism, including cell signaling, immune function, membrane trafficking, and regulation of longevity (42,70). Whereas the mechanism of these processes is only partially understood, much less is known about how the structure of the LD phospholipid monolayer may affect LD protein targeting and function.…”
mentioning
confidence: 99%
“…This chapter describes detailed protocols for such high-throughput analyses that have been used to measure the levels of trehalose, glycogen, ethanol, and acetic acid as well as to quantitatively assess the entire complement of cellular lipids. These metabolites have been shown to play a pivotal role in defining the chronological life span of a yeast cell [8,9,[21][22][23][25][26][27][28]. It should be emphasized that the described here metabolic and lipidomic analyses provide powerful empirical tools for studying mechanisms that underly not only aging but also many other paradigms of yeast biology.…”
Section: Introductionmentioning
confidence: 96%
“…Recent metabolomic and lipidomic analyses of the metabolic history of chronologically aging yeast cells strongly suggest that their longevity is defined by a pattern of metabolism and organelle dynamics established prior to cell entry into a non-proliferative state in a genotype-, diet-, and pharmacological interventiondependent manner [8,9,[20][21][22][23][25][26][27][28]. This chapter describes detailed protocols for such high-throughput analyses that have been used to measure the levels of trehalose, glycogen, ethanol, and acetic acid as well as to quantitatively assess the entire complement of cellular lipids.…”
Section: Introductionmentioning
confidence: 99%